Designing solid waste collection strategy in small municipalities of developing countries using choice experiment - Rajesh Kumar Rai; Dipendra Bhattarai; Sajan Neupane (Journal of Urban Management, 2019)
Household waste management is one of the major challenges of municipalities in developing countries. In many large cities, private service providers deliver the service of household waste collection for a fee, but in smaller cities this service is not always available as it may not be profitable for private providers as a result majority of the waste remains uncollected. Determining a waste collecting fee for the first time is challenging for any municipal authority. In this context, this study conducted a choice experiment (CE) survey to determine household preferences for a household waste collection system in Ilam municipality in eastern Nepal. CE is considered reliable and has increasingly been used to elicit preferences for goods and services. The results indicate that implicit price of the attributes of municipal waste management including waste collection frequency is USD 0.44 for an additional time per month, distance to waste collection center is USD 0.19/minute walk up to seven minutes and subsidy to bin is USD 0.038 for every 10% subsidy increase. Based on the implicit price and different combinations of attributes, households are willingness-to-pay between USD 0.20 to USD 0.75 per month for different household waste collection management schemes. The aggregated maximum willingness-to-pay of municipal households for waste collection services is USD 40,900, which is equivalent to the annual municipal expenditure on sanitation and street light activities.
Keywords: 710; Choice experiment; Collection frequency; Dustbin; Household waste; Willingness-to-pay